1973
DOI: 10.1128/jvi.12.1.61-67.1973
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bacteriophage φ29 Proteins in Bacillus subtilis

Abstract: Seventeen bacteriophage 029 proteins were detected in ultraviolet lightirradiated Bacillus subtilis by autoradiography of polyacrylamide slab gels. The appearance of 429 proteins occurred either before or concomitantly with viral DNA replication. Viral proteins detected early in the infectious cycle consisted of nine polypeptides ranging from 5,200 daltons to 54,000 daltons. Two of the early proteins were identified as, respectively, the major capsid protein and the protein comprising the filaments which exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The genome is a linear, nonpermuted duplex DNA of 12 megadaltons (Mdal), with protein (gp3) covalently bound to the 5' termini (1,2,24,30,31,49,55). Eighteen cistrons have been mapped, and 25 virus-specific proteins, reflecting more than 90% of the coding capacity of the genome, have been identified (5,13,25,38,39,45).…”
mentioning
confidence: 99%
“…The genome is a linear, nonpermuted duplex DNA of 12 megadaltons (Mdal), with protein (gp3) covalently bound to the 5' termini (1,2,24,30,31,49,55). Eighteen cistrons have been mapped, and 25 virus-specific proteins, reflecting more than 90% of the coding capacity of the genome, have been identified (5,13,25,38,39,45).…”
mentioning
confidence: 99%
“…Notably, upregulation of host38's translation genes was also middle/middle late [30], thus suggesting that phage phi38:1 translation in this host is mainly timed with the activation of host translation as occurs with phi18:3 on host18. Given that phage protein translation is expected to closely follow transcription based on lessons from phages infecting (efficiently) well-known systems (e.g., Bacillus phage phi29 synthesizes >60% of its proteins before middle transcription [77]), the inability of phi38:1 to synchronize translation with transcription in host18 may contribute to this inefficient infection.…”
Section: Absence Of Transcriptional-translational Synchronization In mentioning
confidence: 99%
“…imum number of complementation groups reported by an one laboratory is 17 (199); thus even if all cistrons reported by other groups are redundant, this appears to provide a minimum number of polypeptides whose synthesis is directed by 029 DNA. In UV-irradiated B. subtilis infected with 029, up to 23 phage-induced proteins have been separated by gel electrophoresis (48,122,195,227). It is possible, however, that some of the proteins identified on gels may be precursor proteins which are cleaved to generate lower-molecular-weight products which are observed on the same gels (7).…”
Section: Sp82gmentioning
confidence: 99%
“…Studies of phage-directed protein synthesis have been carried out by infecting UV-irradiated B. subtilis with wild-type or mutant 429 in the presence of radioactive amino acids, and subsequently separating the isolated proteins on polyacrylamide gels. Using this technique Carrascosa et al (47) detected 12 nonstructural proteins in addition to seven structural components; Pene and co-workers (227) found seven structural proteins and as many as 10 early and four late nonstructural polypeptides. Moreover, this latter group found that synthesis of six of the early nonstructural proteins ceased late in infection, and they suggest these proteins may be related to the early 750,000-molecularweight RNA transcript which is shut off at the time DNA synthesis is initiated.…”
Section: Development Of 4o29 429 Infection Has Little Effect On Host mentioning
confidence: 99%